Motif Invasi Militer Arab Saudi Terhadap Yaman pada Tahun 2015 - Moh. Zuhri (HI 16 UMY 196, 2016)
*196 This paper tries to explain some factors that push Saudi Arabia to do Military Invasion towards Yemen in 2015. The method used in this research is descriptive analytic method. Data collection techniques gathered from secondary data from books, the internet, journals, articles, written reports, magazines, and other documents were analyzed qualitatively. During invading Yemen, Saudi Arabia gets fully support from Hai’ah Kibarul Ulama. Besides, the official request from President Mansour Hadi is also a legitimate factor for Saudi Arabia to invade Yemen. Geographically, the conflict in Yemen is a threat for Saudi Arabia. Economically, Saudi Arabia’s investment in Yemen needs protecting. The conflict in Yemen causes the investment get stucked